A Review of Commercialization Tools: University Incubators and Technology Parks - Jamil, Farhan; Ismail, Kamariah; Mahmood, Nasir (International Journal of Economics and Financial Issues, 2015)
In recent years, commercialization has gained significant importance due to its active participation in knowledge transfer, economic growth, job creation and entrepreneurship. Whereas the role of university incubators and technology parks to excel commercialization has also much evidence. This study reviews the roles, practices, functions, factors and dimensions of the commercialization, university incubators and technology parks. During review, it come to surface that property development, networking with local and international markets, research and development, proximity to university, firm's clustering, provision of advanced equipments, managerial support, faculty and students, and institutional reputation are the most important elements of university incubators and technology parks to promote commercialization. However, various challenges such as lack of human expertise and insufficient financial capital are still exists which requires to be further studied to upraise the commercialization efficacy. Keywords: Commercialization, University Incubators; Technology Parks; Knowledge Transfer; Entrepreneurship JEL Classifications: M00